Measurement properties of health-related quality of life instruments for people living with scoliosis in China: A systematic review - Liu-qing Jing; Qi-xing Shen; Yi-lin Jin; Shao-jie Du; Ting-zhen Liu; Ni Chen; Guo-dong Wang; Wen Mo; Jie Ye; Jin-hai Xu (PLoS ONE, 2025)
Purpose Scoliosis is a three-dimensional structural deformity of the spine that leads to restricted spinal motion, weakness in the paraspinal muscles, reduced cardiopulmonary function, and chronic physical and psychological pain. It also impacts patients’ quality of life. According to statistics, as of 2022, the number of Chinese primary and secondary school students with scoliosis has exceeded 5 million, and continues to grow at an annual rate of approximately 300,000 new cases, while the incidence of scoliosis in adults is even higher. Therefore, it is crucial to evaluate health-related quality of life (HR-QoL) in this population. This systematic review examined the frequency of use of HR-QoL outcome measurement instruments among patients with scoliosis in China and synthesized evidence on their measurement properties. Methods Stage 1: We searched databases including MEDLINE, EMBASE, Scopus, PubMed, and the Web of Science from inception to December 2023 to identify studies that examined HR-QoL among patients with scoliosis in China. A list of patient reported outcome measures used in clinical HR-QOL measurement for this population was derived from the selected studies. Stage 2: Reporting followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) and AMSTAR (Assessing the methodological quality of systematic reviews) Guidelines. First, we used the COSMIN checklist to assess the methodological quality of studies that reported the measurement properties of the patient reported outcome measures used. Second, the COSMIN tool was used to assess the measurement properties of these instruments, and ratings (excellent, good, fair, or poor) were assigned for each measurement property. Finally, the best evidence was synthesized. Results In total, 155 studies were included, and 47 instruments were identified. The top five frequently used HR-QoL instruments for patients with scoliosis in China were the C-SRS-22, ODI, VAS, SF-36, and TC-SRS-22r. The measurement properties assessed included internal consistency (12 instruments), reliability (13 instruments), construct validity (9 instruments), ceiling and floor effects (8 instruments), and responsiveness (3 instruments). The C-ISYQOL had the best methodological quality. No studies assessing measurement properties of instruments for adults with scoliosis were found. Conclusions Based on limited research evidence, the C-ISYQOL currently demonstrates the best measurement performance among HR-QoL assessment instruments for Chinese scoliosis patients. However, due to potential publication bias resulting from the restriction of literature searches to published works (excluding grey literature), as well as minor impacts that strict adherence to COSMIN guidelines may still exert on measurement evaluations due to their inherent limitations, the number of studies supporting the favorable measurement properties of the C-ISYQOL remains insufficient. Therefore, it cannot currently be recommended as the preferred instrument for clinical measurement. Although the C-SRS-22 is widely used and has good reliability and validity for HR-QoL assessment in adolescent patients with scoliosis, its measurement properties have not been adequately evaluated in adult populations, and it is not currently supported for use in HR-QoL assessment of adults with scoliosis. Further studies assessing the measurement properties of these instruments are urgently needed.